Analysis of Macroeconomic Indicators Against the Composite Stock Price Index (CSPI) in Indonesia: Vector Error Correction Model (VECM) Approach - Afla Afifa Aminarta; Mahrus Lutfi Adi Kurniawan (Journal of Economics Research and Social Sciences, 2021)
The Composite Stock Price Index (CSPI) is one indicator to determine economic growth. The Composite Stock Price Index (CSPI) is formed by counting the stocks listed on the Indonesia Stock Exchange (IDX). Macroeconomic conditions can influence the movement of the CSPI in a country. Macroeconomic indicators that affect the CSPI include inflation, exchange rates, and interest rates represented by the BI rate. This study aimed to determine how much influence the selected macroeconomic indicators had on the CSPI and determine the CSPI movement forecast. This study uses the Vector Error Correction Model (VECM) as an estimation method. The research shows that the inflation, exchange rate, and BI rate variables do not affect the CSPI in the short term, and only the exchange rate variable affects the long term. Forecasting performed on variables shows an over-optimistic forecast for the exchange rate and BI rate variables.